2017
DOI: 10.1158/1535-7163.mct-17-0385
|View full text |Cite|
|
Sign up to set email alerts
|

MiR-125b Increases Nasopharyngeal Carcinoma Radioresistance by Targeting A20/NF-κB Signaling Pathway

Abstract: Radioresistance poses a major challenge in nasopharyngeal carcinoma (NPC) treatment, but little is known about how miRNA regulates this phenomenon. In this study, we investigated the function and mechanism of miR-125b in NPC radioresistance, one of upregulated miRNAs in the radioresistant NPC cells identified by our previous microarray analysis. We observed that miR-125b was frequently upregulated in the radioresistant NPCs, and its increment was significantly correlated with NPC radioresistance, and was an in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 49 publications
0
19
0
Order By: Relevance
“…A number of studies have reported that miRNAs can serve roles as tumor suppressors and oncogenes. Aberrant expression levels of miRNAs and genes have been detected in NPC in a number of studies; several miRNAs are upregulated in NPC, including miR-27a-3p (21), miR-93 (22) and miR-125b (23), and certain miRNAs are downregulated in NPC, including miR-135a (10), miR-203a-3p (12) and miR-185 (24). The present study demonstrated that the expression levels of miR-212 were significantly lower in NPC tissues and cell lines compared with normal controls.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have reported that miRNAs can serve roles as tumor suppressors and oncogenes. Aberrant expression levels of miRNAs and genes have been detected in NPC in a number of studies; several miRNAs are upregulated in NPC, including miR-27a-3p (21), miR-93 (22) and miR-125b (23), and certain miRNAs are downregulated in NPC, including miR-135a (10), miR-203a-3p (12) and miR-185 (24). The present study demonstrated that the expression levels of miR-212 were significantly lower in NPC tissues and cell lines compared with normal controls.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, miR-125b belongs to the miR-17-92 cluster and has been reported to act as an oncogene in several human malignancies. Wang et al demonstrated that miR-125b was overexpressed in nasopharyngeal carcinoma (32). Shen et al reported that the expression of miR-125b was markedly increased in type II diabetes mellitus (33).…”
Section: Discussionmentioning
confidence: 99%
“…Inactivation of PTEN results in constitutive activation of the STAT3 and PI3K-AKT pathways and subsequent protein synthesis, inhibiting apoptosis. Experiments have shown that Bcl-2 protein levels are increased in miR-205 transfected CNE-2 cells, and studies have shown that STAT3 activation can inhibit cell apoptosis by blocking the expression of Bim protein [50,51]. However, miR-185, which enhances apoptosis, can increase the expression of Bax and Bid and decrease the expression of Bcl-2, promoting apoptosis, [52].…”
Section: Mirnas Participate In Radiotherapy Resistance Of Nasopharyngmentioning
confidence: 99%